Partitioning of Cu between mafic minerals, Fe–Ti oxides and intermediate to felsic melts. (15th February 2015) - Liu, Xingcheng; Xiong, Xiaolin; Audétat, Andreas; Li, Yuan
Abstract: This study used improved capsule technique i.e., Pt95 Cu05 or Au95 Cu05 alloy capsules as Cu sources to determine Cu partitioning between mafic minerals, Fe–Ti oxides and intermediate to felsic melts at 0.5–2.5 GPa, 950–1100 °C and various oxygen fugacities ( f O2 ). In combination with the data from the mafic composition systems, the results demonstrate that Cu is generally highly incompatible in mafic minerals and moderately incompatible to compatible in Fe–Ti oxides. The general order of mineral/melt Cu partition coefficients (DCu ) is garnet (0.01–0.06) ⩽ olivine (0.04–0.20) ≈ opx (0.04–0.24) ≈ amphibole (0.04–0.20) ⩽ cpx (0.04–0.45) ⩽ magnetite, titanomagnetite and Cr-spinel (0.18–1.83). The variations in DCu depend mainly on temperature, f O2 or mineral composition. In general, DCu for olivine (and perhaps opx) increases with decreasing temperature and increasing f O2 . DCu increases for cpx with Na + (pfu) in cpx, for magnetite and Cr-spinel with Fe 3+ (pfu) in these phases and for titanomagnetite with Ti 4+ (pfu) in this phase. The large number of DCu data (99 pairs) serves as a foundation for quantitatively understanding the behavior of Cu during magmatic processes. The generation of intermediate to felsic magmas via fractional crystallization or partial melting of mafic rocks (magmas) at deep levels of crust involves removal of or leaving assemblages of mafic minerals + Fe–Ti oxides ± sulfides. With our DCu data on mafic minerals and Fe–Ti oxides, D Cu bulk values around 0.2 were obtained for the sulfide-free assemblages. Cu will thus be concentrated efficiently in the derived melts during these two processes if sulfides are absent or negligible, explaining that high f O2 and sulfide-destabilization are favorable to formation of the porphyry Cu system.